Sunday

March 29, 2015

March 29, 2015

Posted by **Embraced** on Tuesday, January 10, 2012 at 9:00pm.

- Algebra 2 -
**Reiny**, Tuesday, January 10, 2012 at 9:14pmlet n=1 -- 1-3 = -2

let n=2 -- 2-3 = -1

let n=3 -- 3-3 = 0

let n=4 -- 4-3 = 1

let n=5 -- 5-3 = 2

then

-2 + (-1) + 0 + 1 + 2 = 0

**Answer this Question**

**Related Questions**

Algebra - Express the sum below using summation notation. Use 1 as the lower ...

Algebra - How do I write the terms of the series and find the sum. 4 summation ...

Algebra 2 - Write the series with summation notation 3+9+19+33+51+73 I'm not ...

chemistry - How do I calculate the average Z molar mass, 1/n (Summation) of n*M ...

algebra 2 - A skier has decided that on each trip down a slope, she will do 2 ...

Calculus 2 - In the following series x is a real number. In each case, use the ...

CALC 2 - In the following series x is a real number. In each case, use the ratio...

CALC 2 pls help!! - In the following series x is a real number. In each case, ...

Algebra 2 - What is the summation of (n-3) from n=1 to n=5?

Maths - I have a summation formula for Fibonacci numbers. n (SUM)F(2i)=F(2n+1)-1...